Water Relations and Foliar Isotopic Composition of Prosopis tamarugo Phil., an Endemic Tree of the Atacama Desert Growing at Three Levels of Water Table Depth - Garrido, Marco; Silva, Paola; Acevedo, Edmundo (Frontiers in Plant Science, 2016)
Prosopis tamarugo Phil. is a strict phreatophyte tree species endemic to the "Pampa del Tamarugal”, Atacama Desert. The extraction of water for various uses has increased the depth of the water table in the Pampa aquifers threatening its conservation. This study aimed to determine the effect of the groundwater table depth on the water relations of P. tamarugo and to present thresholds of groundwater depth (GWD) that can be used in the groundwater management of the P. tamarugo ecosystem. Three levels of GWD, 11.2 ± 0.3 m, 10.3 ± 0.3 m and 7.1 ± 0.1 m, (the last GWD being our reference) were selected and groups of 4 individuals per GWD were studied in the months of January and July of the years 2011 through 2014. When the water table depth exceeded 10 m, P. tamarugo had lower pre-dawn and midday water potential but no differences were observed in minimum leaf stomatal resistance when compared to the condition of 7.1 m GWD; the leaf tissue increased its δ13C and δ18O composition. Furthermore, a smaller green canopy fraction of the trees and increased foliage loss in winter with increasing water table depth was observed. The differences observed in the physiological behavior of P. tamarugo trees, attributable to the ground water depth; show that increasing the depth of the water table from 7 to 11 m significantly affects the water status of P. tamarugo. The results indicate that P. tamarugo has an anisohydric stomatal behaviour and that given a reduction in water supply it regulates the water demand via foliage loss. The growth and leaf physiological activities are highly sensitive to GWD. The foliage loss appears to prevent the trees from reaching water potentials leading to complete loss of hydraulic functionality by cavitation. The balance achieved between water supply and demand was reflected in the low variation of the water potential and of the variables related to gas exchange over time for a given GWD. This acclimation capacity of P. tamarugo after experiencing increases in GWD has great value for the implementation of conservation strategies. The thresholds presented in this paper should